World class key account management - Ryals, Lynette (Henry Stewart Talks, 2010)
Why KAM is the most important development in business-to-business marketing and selling for the past decade, How to identify and prioritise key accounts, Managing a profitable portfolio of key accounts, The skills of a key account manager, Why being good at selling is no guarantee of success in KAM